A new chart for weight control in Duchenne muscular dystrophy. Issue 10 (October 1988) - Griffiths, R D; Edwards, R H
Abstract : Weight control is desirable in the muscle wasting conditions. A new chart is presented to allow the prediction of an ideal weight, free of excess fat, specifically for boys with Duchenne muscular dystrophy.